2016
DOI: 10.5897/ajar2016.11545
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the sensory attributes and the quality of coffee in different environments

Abstract: In order to understand the relationship between the sensory attributes of coffee (including factors such as acidity, flavor, and aftertaste), and given the possible influences of genetic factors on coffee quality, we evaluated the sensory quality of 10 commercial cultivars of Coffea arabica in three important coffee regions of Minas Gerais, Brazil, and examined, via path analysis, the interactions of the attributes that determine coffee quality. The experiments were conducted in three cities (Lavras, Patrocíni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
2
4
0
1
Order By: Relevance
“…These results indicate that higher scores for a sensory attribute imply a higher FSS. The sensory attributes of balance, flavor, aftertaste, and acidity had the highest correlation coefficients with FSS, corroborating the results of other studies (Kathurima et al 2009;Carvalho et al 2016;Pereira et al 2017). Balance represents flavor, aftertaste, acidity, and body attributes present in equal proportions (Lingle and Menon 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results indicate that higher scores for a sensory attribute imply a higher FSS. The sensory attributes of balance, flavor, aftertaste, and acidity had the highest correlation coefficients with FSS, corroborating the results of other studies (Kathurima et al 2009;Carvalho et al 2016;Pereira et al 2017). Balance represents flavor, aftertaste, acidity, and body attributes present in equal proportions (Lingle and Menon 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Fassio et al (2016) evaluated C. arabica cultivars with different levels of rust resistance and found that the cultivars Araponga MG1, Catiguá MG2, and Catiguá MG1 were the most suitable for producing specialty coffees in Minas Gerais. Carvalho et al (2016) also highlighted the potential of the cultivars Araponga MG1 and Catiguá MG2 in Minas Gerais. Other studies have confirmed the genetic potential of sensory qualities of rust-resistant coffee genotypes in Minas Gerais (Sobreira et al 2016;Barbosa et al 2019;Pereira et al 2019).…”
Section: Discussionmentioning
confidence: 88%
“…The sum of the attribute scores represented the final score of beverages (Fsc), allowing for the final classification of the drink. Each sample began with a pre-established score of 36 points, which incorporated the notes of each attribute, and samples with a score higher than 80 were classified as specialty coffee (Carvalho et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…These results show a potential relationship between GD, phenotypic mean, and combining ability. In addition, Catiguá MG2 has been used as a source to enhance cup quality and obtain specialty coffee (Alex et al, 2016;De Paiva Barbosa et al, 2019b). This cultivar has also been highlighted for its high resistance to CLR (Del Grossi et al, 2013) and moderate resistance to bacteriosis caused by Pseudomonas syringae (Fernandes et al, 2020).…”
Section: Diallel Analysismentioning
confidence: 99%